4.0k views
1 vote
What is the solution to this system of linear equations?

2x + y = 1
3x – y = –6

(–1, 3)

(1, –1)

(2, 3)

(5, 0)

User Mark Kanof
by
5.1k points

2 Answers

2 votes

x = -1

y = 3

2x + y = 1 (eq no 1)

3x - y = -6 (eq no 2)

solve eq no 1

y = 1 - 2x (eq no 3)

enter eq no 3 into eq no 2

3x - ( 1 - 2x ) = -6

3x - 1 + 2x = -6

5x = -5

x = -5/5

x = -1

enter x = -1 into eq no 1

2 (-1) + y = 1

-2 + y = 1

y = 3

User JBJ
by
4.4k points
2 votes

Answer:

A. (-1,3)

Hope this helps :D

User Langsmith
by
4.5k points